AWARENESS AND ATTITUDE OF ISLAMIYYAH SCHOOLS OF INCLUSIVE EDUCATION IN SOUTH WEST, NIGERIA - Yahya, Isiaq Oluwatosin; Olaniyan-Shobowale, Khadijah Olushola; Owoyale-Abdulganiy, Ibrahim Solahudeen; Abdul-Rafiu, Jamiu,; Sanni, Hajarah Monisola (JURNAL EDUSCIENCE, 2023)
This study assessed the Awareness and Attitude of Islamiyyah Schools on Inclusive Education in South West, Nigeria. This study adopted descriptive research design. The population consists of all the teachers and school leaders available in all Islamiyyah Schools in South west, Nigeria out of which five Islamiyyah Schools (30 across all states), 25 respondents (150 across all states) were selected as using disproportionate random sampling technique. The instruments used for collection of data is a self-constructed questionnaire titled "Questionnaire on Awareness and Attitude of Islamiyyah Schools on Inclusive Education in South west, Nigeria (QAAISIESWN). The study reveals a notable low level of awareness among Islamiyyah schools regarding inclusive education. The findings underscore a critical need for targeted awareness campaigns and policy reforms to align with the principles of inclusivity in among Muslim youth schools in the sub region. Here are recommendations addressing the identified issues within Islamic youth and special education needs within Islamiyyah Schools.